The Role of the Banking Industry in Achieving Regulatory Brilliance- Evidence from Commercial Banks in Jordan - Yousef Bani Hani, Laith; Jerri Mohsin, Hayder; Aldeen Kassem Al-Alawnh, Noor; Saleem Al-Shdaifat, Muna; Khaled Alzu'bi, Sara; Adel Quraan, Awad (South Asian Journal of Social Sciences and Humanities, 2023)
This study constitutes a relatively new area, the aim of this research is to identifywhether the use of technology (Banking Industry) in banking leads to regulatory brilliance. Recently, banks have become interested in developing the banking industry and looking for everything new to increase efficiency and improve banking performance and its positive impact on individuals and institutions, the evolution of the banking industry has contributed to multiple solutions to many things; Therefore, creating a suitable banking environment for the sheer scale of development helps organizations towards creativity and thus to achieve organizational brilliance. This study aims to develop the concept of banking industry and its key role in creating a comprehensive and integrated environment and thus to promote the banking sector by introducing the concept of regulatory brilliance. Therefore, a sample of Jordanian commercial banks was selected through our study, and it was distributed to workers (Bank Managers, Clients Departments & Accountants) a questionnaire of (200) forms which includes (30) questions, then an analysis of the questionnaire that was distributed to banks employees and the search sample included the independent variable which is the banking industry and its dimensions (technology, time, cost) and the dependent variable which is regulatory brilliance and its dimensions (brilliance in service and innovation, brilliance in leadership, brilliance in knowledge).The study shows the interrelationship between the banking industry and its development to achieve the regulatory brilliance in the banks.
Keywords: Banking Industry; Regulatory Brilliance; Jordanian Commercial Banks